O canto coral na educação musical: análise e catalogação a partir das publicações nos anais da ABEM e da ANPPOM, e na Revista da ABEM e Revista OPUS (2009 a 2013) - Santos, Bruno Silva (2014)
Knowing the importance of the choral singing in the formation of the human being, this work aims to catalog and analyze all the articles about choral singing in the musical education, found in the Annals of ABEM and of ANPPOM, and in the ABEM magazine and OPUS magazine, in the period between 2009 and 2013. For the realization of this research, the bibliography research was used as a methodological resource that consists in reading, analyzing and interpreting the publications with the intention of serving as a theoric base of the purposed study. In total, 64 publications were found about the theme, that contain contents about socialization, vocal technique, body rhythm, teaching and learning, skills of the conducting professional, among others, that were properly reviewed and analyzed, having its results explained in graphics, that brought the conclusions described on this work.